2022
DOI: 10.1111/jocd.14732
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparative study of the effect of fractional CO2 laser combined with pulsed dye laser versus each laser alone on the treatment of hypertrophic scar of rabbit ears

Abstract: Background and Objective The use of fractional CO2 laser and pulsed dye laser (PDL) therapy to treat and/or prevent scarring following burn injury is becoming more widespread with a number of studies reporting reduction in scar erythema and pruritus following treatment with lasers. The objective of this study was to directly compare the efficacy of PDL, fractional CO2, and PDL and fractional CO2 laser therapy in immature red hypertrophic scars in a standardized animal model. Methods Ten New Zealand big‐eared r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In another study, the PDL and fractional CO 2 lasers were equally effective in the treatment of hypertrophic scars 11 . In the experimental study, the authors found that VEGF expression in the composited laser group was weaker than that in the PDL group and fractional CO 2 group at 7 days, 14 days, and 28 days after treatment, with significant differences between the groups 37,39 . Fractional CO 2 laser can increase the apoptosis of fibroblasts, promote collagen degradation, and reduce the secretion of VEGF by epidermal cells, so as to inhibit the proliferation of microvessels and promote the maturation and vascular regression of hypertrophic scar 40–42 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study, the PDL and fractional CO 2 lasers were equally effective in the treatment of hypertrophic scars 11 . In the experimental study, the authors found that VEGF expression in the composited laser group was weaker than that in the PDL group and fractional CO 2 group at 7 days, 14 days, and 28 days after treatment, with significant differences between the groups 37,39 . Fractional CO 2 laser can increase the apoptosis of fibroblasts, promote collagen degradation, and reduce the secretion of VEGF by epidermal cells, so as to inhibit the proliferation of microvessels and promote the maturation and vascular regression of hypertrophic scar 40–42 .…”
Section: Discussionmentioning
confidence: 98%
“…36 Chen et al demonstrated that the combination of PDL and fractional CO 2 laser could improve the treatment effect on red hypertrophic scars, partly by regulating the expression of vascular endothelial growth factor (VEGF), through morphological observation and histological experiments. 37 Zhang et al demonstrated that the combination of 595-nm PDL and fractional CO 2 laser could better improve the scar condition over mono-application, partly through the inhibition of expression of proliferating cell nuclear antigen and transforming growth factor-β1. 38 In another study, the PDL and fractional CO 2 lasers were equally effective in the treatment of hypertrophic scars.…”
Section: Posasmentioning
confidence: 99%
See 1 more Smart Citation
“…This caused a change in the shape and histology of the rabbit model's hypertrophic scar. Chen, H. Y 45 . discovered that the effect of a dot matrix CO2 laser paired with a pulsed dye laser inhibited early hypertrophic fibrosis in rabbit ears better than either the dot matrix CO2 laser or the pulsed dye laser individually.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, randomized control trial found in comparison to control and CO 2 laser alone, treatment with a combination of IPL and fractional CO 2 laser showed greater average improvements in both texture and color across the majority of examined scar domains, indicating by employing a variety of wavelengths to target the different chromophores in scars, a multi-photo-thermolytic approach combining IPL with CO 2 AFL could be successful in treating hypertrophic scars. 57 However, Laura et al looked at hypertrophic burn scars of different ages, origins, and thicknesses. Although greater early decrease is seen in thicker scars when utilizing CO 2 , PDL, or both laser modalities, there was no clinically significant advantage discovered comparing combined therapy to individual therapy.…”
Section: Combination Therapymentioning
confidence: 99%